2018
DOI: 10.1093/scan/nsy064
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the social brain across childhood and adolescence

Abstract: Previous research has characterized a collection of neural regions which support social-cognitive processes. While this ‘social brain’ is often described as a cohesive unit, it has been largely assessed with univariate methodologies, which cannot account for functional relationships ‘between’ brain regions, and therefore cannot test the idea of the social brain as a network. In the present work, we utilized a multi-method approach to empirically assess the functional architecture of the social brain. Fifty par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…In fact, a recent study demonstrated the social brain network to be functionally distinct and robustly recruited in 3-year-old children, independent from explicit mentalizing skills [61]. Similarly, a recent study in 50 children and adolescents did not find an effect of age on several measures of functional connectivity of the social brain [62]. Overall, these and our findings suggest that across study populations, the core neurofunctional network for mentalizing is largely set by the age of 6 and does not undergo gross changes from mid-childhood to adulthood.…”
Section: Effects Of Agementioning
confidence: 95%
“…In fact, a recent study demonstrated the social brain network to be functionally distinct and robustly recruited in 3-year-old children, independent from explicit mentalizing skills [61]. Similarly, a recent study in 50 children and adolescents did not find an effect of age on several measures of functional connectivity of the social brain [62]. Overall, these and our findings suggest that across study populations, the core neurofunctional network for mentalizing is largely set by the age of 6 and does not undergo gross changes from mid-childhood to adulthood.…”
Section: Effects Of Agementioning
confidence: 95%
“…Marked improvement in social cognitive skills during childhood and adolescence is generally considered to be the dominant developmental focus of this highly dynamic age range (Blakemore, 2008). The brain regions implicated in "the social brain" are some of the most densely connected in the cortex (McCormick et al, 2018;Oldham and Fornito, 2019;Saxe et al, 2009), and previous studies have shown that significant changes in FC organization of these regions occurs during development (Richardson et al, 2018). Recently, Lake et al used Connectome Predictive Modeling to identify a complex set of FC edges that predict SRS scores in a large sample of children and adolescents with and without autism spectrum disorder (Lake et al, 2019).…”
Section: Social Scores and Functional Connectivitymentioning
confidence: 99%
“…Independent Component Analyses confirmed that the pSTS activation in this study was a part of a larger network (IC 26), the social brain network, which was composed of social brain nodes such as the pSTS, bilateral DLPFC, and right temporoparietal junction. DLPFC can be explained as coactivated region of social brain network due to correlation between social brain network and fronto-striatal connectivity (McCormick et al, 2018). Besides the pSTS, the AIC also is known to take part in social processing.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying neurodevelopmental vulnerability of adolescent brain, such as functional gaps between networks and insufficient segregation of networks (Stevens, 2016), might also play an important role in the neurobiological changes induced by excessive social stimuli. Considering that the social brain network is early-developed compared to other functional networks (Dunbar & Shultz, 2007;McCormick et al, 2018), we suppose that the functional gap between the social network and cognitive network is related to sensitive social perception to excessive social stimuli resulting in increased functional connectivity between salience network and social brain network in IGD. Aberrant functional connectivity of social brain network to other intrinsic networks might also be associated with insufficient segregation during brain maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation